The impact of ethical ideologies on the judgment of online marketing communications ethics in the tourism market tourism students’ perspective - Lončarić, Dina; Balent, Mateja (2019)
The purpose of this paper is to study the relationship between ethical ideologies and the judgment of online marketing communications ethics in the tourism market. The aim of the research is also to establish a relationship between the judgement of online communications ethics and behavioural intentions. The paper is based on empirical research conducted using the scenario method and survey method. The Ethics Position Questionnaire (EPQ) was used to measure ethical ideology along two dimensions, relativism and idealism. Five scenarios were designed, describing potentially ethically ambiguous situations. A relationship was established between ethical ideologies and ethical judgements of online marketing communications. The study proved that respondents who scored higher on the idealism scale have more rigid criteria with regard to online communications ethics and were better at recognising ethically ambiguous situations. A relationship between the ethical judgements of the described situations and behavioural intention was also established. Although topics relating to online communications on the tourism market are extensively researched, there are few studies dealing with ethical judgement of such communications. The special contribution of this paper is in the fact that research includes students of tourism and hospitality who will, in the near future, find themselves in situations where they will need to make, and take moral responsibility for, decisions regarding communications in the tourism market. Therefore, this research contributes both to theory and practice.
Svrha rada je istražiti povezanost između etičkih ideologija i prosudbe etičnosti online marketinške komunikacije na turističkome tržištu. Cilj je istraživanja, također, utvrditi povezanost između prosudbe etičnosti komunikacije na internetu i namjere ponašanja. Rad se temelji na empirijskom istraživanju u kojemu su primijenjene metoda scenarija i metoda ispitivanja. Kao instrument istraživanja korišten je Upitnik etičke pozicije (EPQ) kojim su mjerene etičke ideologije uvažavajući dimenzije relativizma i idealizma. Oblikovano je pet scenarija kojima su opisane potencijalne etički dvojbene situacije. Utvrđena je povezanost između etičkih ideologija i prosudbe etičnosti u online marketinškoj komunikaciji. Istraživanje je dokazalo da ispitanici koji ostvaruju više rezultate na ljestvici idealizma imaju strože kriterije u odnosu na etičnost u online komunikaciji i bolje raspoznaju etički dvojbene situacije. Utvrđena je i povezanost između prosudbe etičnosti opisanih scenarija i namjera ponašanja. Iako su teme u području internetske komunikacije na turističkome tržištu do sada istraživane, ima malo studija koje se odnose na prosudbu etičnosti takve komunikacije. Poseban doprinos ovoga rada očituje se u činjenici da su istraživanjem obuhvaćeni stavovi studenata turizma i ugostiteljstva koji će se u bliskoj budućnosti i sami naći u situacijama u kojima će trebati preuzeti moralnu odgovornost za odluke u vezi s komunikacijom na turističkome tržištu. Ovo istraživanje, stoga, daje doprinos i teoriji i praksi.
Bibliografija: str. 143-146.
Summary ; Sažetak.
Keywords: Marketinška etika -- Etičke ideologije -- Internetska komunikacija -- Turizam